Immediate Action Required: Legal Measures for Occupations Changed from the COVID-19 Pandemic - Saisombat, Phetcharat; Apichatsakol, Prapee (Rajapark Journal, 2024)
This comprehensive study aimed to investigate 1) the types of jobs during a COVID-19 pandemic in Thailand, 2) the factors associated with altering types of occupations during a COVID-19 pandemic, and 3) the government welfare benefits offered after informal workers’ employment changed. This quantitative study collected data through a questionnaire using purposive sampling. The quantitative data were analyzed using descriptive statistics, including frequency, percentage, and mean and inferential statistics. The research also raises questions regarding domestic and international laws, regulations, and measures related to informal workers. The survey discovered that the sample’s average age was 29 years, and over one-third were now unemployed. Many in the sample group who had jobs before the epidemic became unemployed and no longer working (69.4%). Regarding occupational patterns, older persons are less likely to change careers since they have more job security, work experience, and the ability to adjust to changing circumstances. Meanwhile, younger people, or the new generation, are more inclined to choose jobs that match their interests. Regarding work careers, it was discovered that people with no job limits and who could explore extra employment were more likely to modify their career patterns. The COVID-19 pandemic has significantly impacted the working-age population, particularly those working in the informal sector, because they have no employer or social protection. As a result, these workforce groups continue to require more excellent government help than others. As a result, the government should extensively promote knowledge of benefits to the working population, particularly in informal sectors, because welfare rights are essential to them. Currently, no law explicitly supports this.